2013
DOI: 10.2174/1389557511313070010
|View full text |Cite
|
Sign up to set email alerts
|

Recent Approaches in Design of Peptidomimetics for Antimicrobial Drug Discovery Research

Abstract: Resistant pathogenic microbial strains are emerging at a rate that far exceeds the pace of new anti-infective drug development. In order to combat resistance development, there is pressing need to develop novel class of antibiotics having different mechanism of action in comparison to existing antibiotics. Antimicrobial peptides (AMPs) have been identified as ubiquitous components of innate immune system and widely regarded as a potential source of future antibiotics owing to a remarkable set of advantageous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Moreover, they are widely regarded as a potential source of future antibiotics owing to a remarkable set of advantageous properties ranging from a broad spectrum of activity to a low propensity for resistance development (17). The major human cationic host defense peptide is LL-37 (Table 1).…”
mentioning
confidence: 99%
“…Moreover, they are widely regarded as a potential source of future antibiotics owing to a remarkable set of advantageous properties ranging from a broad spectrum of activity to a low propensity for resistance development (17). The major human cationic host defense peptide is LL-37 (Table 1).…”
mentioning
confidence: 99%
“…It is important to point out in this connection that compounds of (poly)cationic nature are not unprecedented as antibacterials. Indeed, aminoglycosides and small cationic antimicrobial peptides are naturally occurring antibacterial agents, with the latter class of compounds being regarded as an emerging source of new antimicrobials [84,85]. Furthermore, to overcome some of their drawbacks (e.g., susceptibility of protease-induced cleavage), peptidomimetics are A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 28 currently being explored with some of them in clinical trials [84][85][86].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, aminoglycosides and small cationic antimicrobial peptides are naturally occurring antibacterial agents, with the latter class of compounds being regarded as an emerging source of new antimicrobials [84,85]. Furthermore, to overcome some of their drawbacks (e.g., susceptibility of protease-induced cleavage), peptidomimetics are A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 28 currently being explored with some of them in clinical trials [84][85][86]. In addition, it is noteworthy that guanidine-containing compounds including small peptides and peptidomimetics harbouring one or more guanidino or arginine moieties are of immense interest as drugs targeting a variety of disorders and diseases [87].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…21,22 The biorecognition abilities of peptoids have been demonstrated through two decades of peptoid therapeutics research, protein-binding sequence discovery, and secondary structure design, which have been recently reviewed elsewhere. 10,15,[24][25][26][27] As originally envisioned, 7 many bioactive sequences have been discovered by screening peptoid libraries. 8,13 These include antimicrobial peptoidsÑa significant area of peptoid research discussed in recent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…8,13 These include antimicrobial peptoidsÑa significant area of peptoid research discussed in recent reviews. 10,25,27 Recent studies have also demonstrated peptoid sequences potentially useful in diagnosing or treating amyloid diseases.…”
Section: Introductionmentioning
confidence: 99%